Trust plays no role in regional U.S. economic development—And five other problems with the trust literature. - Forrester, Andrew C.; Nowrasteh, Alex (Kyklos, 2023)
Economists have developed a vast empirical literature on how cultural traits like generalized trust affect economic output. Much of this literature finds a positive causal relationship between measures of generalized trust, as gathered by international surveys, and economic output. However, the trust literature commits five deadly empirical and theoretical sins that undermine many of its findings. From the quality of the survey questions and responses to the paucity of theoretical models used to explain how trust affects economic outcomes to the radically different results from experimental evidence and others, the trust literature is riven with poor methods and bad data. Even so, applying common methods used in the trust literature to regional level analysis in the United States during the 1972–2018 period reveals no statistically significant correlation between economic output and trust. Given our lack of findings at the subnational level, we find further evidence to be skeptical of the trust literature.